Exploring the Green Horizon: Recent Research on Renewable Energy in Poland—A Review - Barış Aydın; Kinga Stecuła; Piotr Olczak; Jarosław Kulpa; Beniamin Stecuła (Energies)
This paper identifies and examines the latest research on renewable energy in Poland, reviewing articles published between 2021 and 2023 indexed in the Scopus database. It analyzes 124 papers, categorizing them into 11 thematic areas which include (1) energy production, (2) energy consumption, (3) energy policy, (4) sustainable development activities, (5) technology and engineering, (6) energy storage, (7) powering vehicles, (8) awareness and attitude regarding energy, (9) finances and investments, (10) emission, and (11) other. The main objective was to analyze the state of the current research on renewables in Poland. The results highlight significant progress in renewable energy capacity, particularly in wind and solar power, driven by national policies, EU funding, and growing public support. The analysis also reveals persistent challenges related to technology, infrastructure, and policy. The authors critically evaluate the research’s relevance to Poland’s energy sector and globally. They also refer to issue of non-renewable energy sources, which, despite the development of the RES sector, still play a dominant role in the Polish energy economy. Due to this, the article not only describes the state of knowledge, but also formulates conclusions on the real needs and opportunities for the further development of energy in Poland.